Influence of incentive mechanism and fit degree on user’s environmental behavior—Taking Alipay “Ant Forest” in China as an example - Xiong, Na; Ren, Ping; Sun, Bingteng; He, Surong; Jiang, Linli; Cui, Haitao (Frontiers in Psychology, 2022)
How to use game elements to motivate users and influence their behavior has become a new research trend, which is vital for enhancing the willingness of potential platform users to participate in environmental protection. This paper aims to analyze the influence of incentive mechanism and fit degree on user’s environmental behavior based on the stimulus-organism-response theory and self-determination theory. The questionnaire data of 500 users was collected and the impact of incentives on user’s environmental behavior was analyzed by structural equation modeling. The results show that economic, value, and social incentives have a significant impact on user’s environmental behavior. Besides, the value and social incentives of “Ant Forest” game platform positively influence user fit (conscious participation, enthusiasm, and platform interaction), but the impact of economic incentive on platform interaction is not statistically significant. From the perspective of user fit, “Ant Forest” game platform can positively promote users to adopt environmental behavior, because it explores users’ needs from their perspective to give full play to the role of game incentives on users' environmental behavior. Additionally, this research provides the practical implications for managers exploring the effects of co-creation processes in developing countries and regions.